Wheel Bug, Arilus cristatus (Linnaeus) (Insecta: Hemiptera: Reduviidae) - Frank W. Mead (EDIS)
Contents: Introduction - Synonymy - Distribution - Description and Identification - Life History - Notes on Behavior - Importance as a Predator - Medical Importance - Enemies - Selected References